Hot Chip Challenge: Acute Gastrointestinal Bleeding in a Pediatric Patient on Left Ventricular Assist Device - Kelm, Marcus; Miera, Oliver; Moosmann, Julia (The Thoracic and Cardiovascular Surgeon Reports, 2025)
Gastrointestinal bleeding (GIB) is the most common and potentially life-threatening bleeding complication in pediatric patients on left ventricular assist devices (LVAD), particularly under anticoagulation. We report a 13-year-old female with dilated cardiomyopathy on HeartMate 3 support who developed acute GIB after participating in a “Hot Chip Challenge,” consuming excessive spicy chips. The bleeding required blood transfusion and intensive management. This case highlights the potential impact of lifestyle factors, especially dietary choices, on GIB risk in pediatric LVAD patients.
Keywords: bleeding; coagulation/anticoagulation; cardiomyopathy; circulatory assist devices; pediatric